Increased levels of a mycophenolic acid metabolite in patients with kidney failure negatively affect cardiomyocyte health - Harlacher, Eva; Schulte, Corinna; Vondenhoff, Sonja; Schmitt-Kopplin, Philippe; Diederich, Philippe; Hemmers, Christian; Moellmann, Julia; Wollenhaupt, Julia; Veltrop, Rogier; Biessen, Erik; Lehrke, Michael; Peters, Björn; et al. (Frontiers in Cardiovascular Medicine, 2024)
Chronic kidney disease (CKD) highly increases cardiovascular risk and mortality, and the accumulation of uremic toxins in the circulation upon kidney failure contributes to this increased risk. We thus performed a screening for potential novel mediators of reduced cardiovascular health starting from dialysate obtained after hemodialysis of CKD patients. The dialysate was gradually fractionated to increased purity using orthogonal chromatography steps, with each fraction screened for a potential negative impact on the metabolic activity of cardiomyocytes using a high-throughput MTT-assay, until ultimately a highly-purified fraction with strong effects on cardiomyocyte health was retained. Mass spectrometry and nuclear magnetic resonance identified the metabolite mycophenolic acid-βglucuronide (MPA-G) as responsible substance. MPA-G is the main metabolite from the immunosuppressive agent mycophenolic acid (MPA), which is supplied in the form of mycophenolate mofetil (MMF) to patients in preparation for and after transplantation or for treatment of autoimmune and non-transplant kidney diseases. The adverse effect of MPA-G on cardiomyocytes was confirmed in vitro, reducing the overall metabolic activity and cellular respiration while increasing mitochondrial ROS production in cardiomyocytes at concentrations detected in MMF-treated patients with failing kidney function. With patients with severely reduced kidney function already displaying a highly increased cardiovascular risk, this study draws attention for potential adverse effects of long-term high MMF dosing specifically in these patients.